Philosophia in transitu : między granicami filozofii a filozofią bez granic - Wróblewski, Paweł P. (Uniwersytet Wrocławski. Instytut Filozofii, 2021)
The monograph consists of nine self-contained studies illustrating the 'transboundary character' of philosophy among other disciplines of scientific knowledge (sciences of religion and culture, theology, history, literary studies, psychology, sociology, biology, medicine and health sciences), as well as the semantic changes of selected key philosophical concepts. The volume begins with a chapter revealing the difficulties in reconstructing Plutarch of Cheronea's cosmogony and the eclectic nature of Medioplatonism, especially concerning its religious content components. The next part of the book not only takes up the strictly theological context of St Basil the Great's use of the philosophical apparatus but also demonstrates the full maturity of the patristic reflection on the status of evil, thus allowing for a revision of the a priori assumed significance of many later approaches. Next, the accumulation of adaptations of the "Book of the Apple" in Hebrew, Latin and Arabic cultures is presented: a case points to the consequences of the lack of access to Greek sources in the formation of medieval "legends about Aristotle". The chapter dealing with the demarcation line between religion and science, as drawn by Ibn Rušd in the 12th century in his study of Islam's relation to the philosophical heritage of the Hellenes, is all the more a warning for contemporary scholars. A different type of limited philosophical transit is dealt with in work devoted to the role of images in the mysticism of John of the Cross, the father of Carmel - an important study in the psychology of religious experience. Then, the definition of "transitus" manifests itself in the context of disputes about Cartesianism, to which a comparative analysis of Malebranche's and Arnauld's views on ideas is dedicated. Another example of philosophy "after the passage" is Freudian psychoanalysis with its bridging role towards detailed disciplines; the author of the chapter tries to keep a "golden mean" in defining these relations. The penultimate part of the book, following Roland Bathes, introduces the reader to a new world of myths after myths, threatened by the 'ideologization of language'. Finally, the monograph culminates with a text postulating the aestheticization of patient care relations, i.e. enhancing subjectivity through an interdisciplinary diagnosis of the patient's personal condition
Keywords: philosophy; interdisciplinarity; philosophy of culture; philosophy of religion; philosophy of theology; philosophy of science; philosophy and social sciences; philosophy of healthcare; bioethics; ancient philosophy; patristics; medieval philosophy; the scientific miracle; idea; psychoanalysis; mythology; ethics of responsibility; Plutarch; Basil the Great; Pseudo-Aristotle; The Book of the Apple; Ibn Rušd; John of the Cross; Nicolas Malebranche; Antoine Arnauld; Sigmund Freud; Roland Barthes